1996
DOI: 10.1021/jm950912p
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Studies of 6-(Tetrazolylalkyl)-Substituted Decahydroisoquinoline-3-carboxylic Acid AMPA Receptor Antagonists. 1. Effects of Stereochemistry, Chain Length, and Chain Substitution

Abstract: A series of 6-substituted decahydroisoquinoline-3-carboxylic acids were prepared as excitatory amino acid (EAA) receptor antagonists. These compounds are antagonists at the N-methyl-D-aspartate (NMDA) and 2-amino-3-(5-methyl-3-hydroxyisoxazol-4-yl) propanoic acid (AMPA) subclasses of ligand gated ion channel (ionotropic) EAA receptors. (3S,4aR, 6R,8aR)-6-(2-(1H-tetrazol-5-yl)ethyl)- 1,2,3,4,4a,5,6,7,8,8a-decahydroisoquinoline-3-carboxylic acid (9) is a potent, selective and systemically active AMPA antagonist.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…One such preparation 5 was discovered after a study of a series of 6-substituted decahydroisoquinoline-3-carboxylic acids [17]. Study of the biological activity showed that preparation 5 is an effective mixed antagonist of AMPA -2-amino-3-(3-hydroxy-5-methylisoxazol-4-yl)propionic acid and kainate receptors and at the same time has lower neurotoxicity than known antagonists of AMPA and NMDA (N-methyl-D-aspartic acid) receptors.…”
Section: -Substituted Tetrazoles Isosteric Substitution Of a Carboxmentioning
confidence: 99%
“…One such preparation 5 was discovered after a study of a series of 6-substituted decahydroisoquinoline-3-carboxylic acids [17]. Study of the biological activity showed that preparation 5 is an effective mixed antagonist of AMPA -2-amino-3-(3-hydroxy-5-methylisoxazol-4-yl)propionic acid and kainate receptors and at the same time has lower neurotoxicity than known antagonists of AMPA and NMDA (N-methyl-D-aspartic acid) receptors.…”
Section: -Substituted Tetrazoles Isosteric Substitution Of a Carboxmentioning
confidence: 99%
“…We therefore applied the GluK1 specific agonist (S)-2-amino-3-(5-tert-butyl-3-hydroxy-4-isothiazolyl)propionic acid (ATPA) (Ornstein et al, 1996, Clarke et al, 1997Clarke and Collingridge, 2002;Clarke and Collingridge, 2004) to investigate the influence of this receptor in AMPAR mediated synaptic transmission at A/C synapses. Application of 1 lM ATPA for 5 min induced a synaptic depression which was reversed by wash-out of the drug.…”
Section: Gluk1 Containing Kainate Receptors Suppress Excitatory Transmentioning
confidence: 99%
“…The initial compounds displayed high, although nonselective, affinity for AMPA and NMDA receptors, but through extensive SAR studies, highly potent and selective compounds such as RPR 119990 (159) and RPR 117824 (160) have been identified. At least two classes of amino-acid-containing compounds, based on decahydroisoquinoline-3-carboxylic acid [362] and AMPA [363], have been found to be competitive AMPA receptor antagonists. At least two classes of amino-acid-containing compounds, based on decahydroisoquinoline-3-carboxylic acid [362] and AMPA [363], have been found to be competitive AMPA receptor antagonists.…”
Section: Competitive and Noncompetitive Ampa Receptor Antagonistsmentioning
confidence: 99%